Meteorological conditions of high-mountain part of the Altai Republic: present-day characteristics, estimates if variability, and effect on glacier regime - N. K. Barashkova; M. A. Volkova; I. V. Kuzhevskaya; N. N. Cheredko (Лëд и снег, 2015)
According to some meteorological and glaciological observations using statistical methods of cluster, harmony, and correlation analyses the assessment trends of the Altai mountainous region glaciological indicators and temperature regime have been obtained. The glaciological effect of the atmospheric circulation of the area under review by means of B.L. Dzerdzeevsky’s typing is studied. The temperature field is a good attribute spaces for classification of mountainous areas and identification of representative areas (classes) in the description of the dynamics of glaciers. Annual mass balance of the Malyi Aktru Glacier which is closely associated with amount of the accumulation decreases with the increase of zonal circulation. Warming which began in the mid 1970s has resulted in precipitation increase during the colder period and accumulation values intensity. Low-frequency harmonic with the period of 55–58 years (Quasi-half a century cycle) determined by the position of the planets of the Solar system and 3, 4, 6, 9, 11 years of periodicity (regularity) are revealed practically in all the ranks of indicators. Statistical characteristics of glaciological and climate indicators of the research can be used to predict seasonal, annual and current states of a climatic regime evaluation of the Altai glaciers and water resources in Western Siberia.